COMPARATIVE ANALYSIS OF THE CONCEPT OF TRADITIONAL AND MODERN MUDHARABAH BETWEEN BOOK OF FATH AL-MU’IN AND THE FATWA OF THE NATIONAL SYARI'AH COUNCIL (DSN) OF THE INDONESIAN ULEMA COUNCIL (MUI) - Helmi Maulana; Mela Inalia Rahmah (Fakultas Ekonomi dan Bisnis Islam, Institut Agama Islam Darussalam (IAID) Ciamis, Jawa Barat, INDONESIA, 2020)
The purpose of this study was to compare the concept of mudharabah fatwa of the National Syari'ah Council (DSN) of the Indonesian Ulema Council (MUI), and the Kitab Fath al-Mu’in by Sheikh Zainuddin bin Abdul Aziz al-Malibari. The methodology used is the descriptive qualitative method, which is a research method that is directed to describe the results of research as it is based on a literature study. The study results indicate that (a) the concept outlined in the DSN Fatwa is a legal product (ijma') of Muslim scholars and scholars who are members of the MUI which presents mudharabah rules that Islamic financial institutions must practice. (b) According to the book of Fath al-Mu’in, qiradh is a cooperative transaction in the business world with profits based on an agreement in the contract illustrated with interpersonal coverage, the actors do not describe the collaborative activities carried out between groups. (c) In principle, the concept of Qirâd in the book of Fath al-Mu’in and the concept of Mudharabah in the Fatwa of DSN MUI is the same. The difference lies in the actor or party making the contract. They will create a concept that will be different from the understanding, provisions, terms and pillars, profit provisions, dispute resolution, and the legal side.